Indigenous Ethiopian okra (Abelmoschus esculentus) mucilage: A novel ingredient with functional and antioxidant properties - Gemede, Habtamu Fekadu (Food Sci Nutr, 2018)
Functional and antioxidant properties of mucilage extracted from the pods of eight okra accessions grown in Benishangul‐Gumuz region, Western Ethiopia, were evaluated. This study had shown that the mucilage contents of the pods of eight okra accessions ranged from 1.25 to 3.45 g/100 g. Functional properties of the mucilage of okra pods varied significantly (p < .05) and had respective ranges of bulk density of 0.58–0.64 g/ml; water absorption capacity of 2.45–4.60 ml/g; oil absorption capacity of 0.02–3.64 ml/g; emulsifying capacity of 42.22%–74.45%; emulsion stability of 42.22%–74.45%; foaming capacity of 50.51%–62.50%, and foam stability of 36.04%–54.35%. Total phenolic and flavonoid contents of the mucilage of the pods of okra accessions ranged from 4.66 to 49.93 mg GAE/g and 8.18–18.72 mg CE/g, respectively. The effective concentration (EC (50)) values (mg/ml) of mucilage of okra pods varied from 3.15 to 6.60 and 1.10 to 1.85 for DPPH scavenging and metal‐chelating activity, respectively. The study revealed that the mucilage of the pods of okra accessions was found to exhibit good functional properties and can offer a great potential in various food systems. Particularly, mucilage of the pods from OPA#5 and OPA#7 had desirable water and oil absorption capacities, whereas the mucilage of accession OPA#1 and OPA#6 had high emulsifying and foaming properties. The results also demonstrated that okra pod mucilage had potential sources of natural antioxidant.